Physical exercise increases adult hippocampal neurogenesis in male rats provided it is aerobic and sustained. (24th February 2016) - Nokia, Miriam S.; Lensu, Sanna; Ahtiainen, Juha P.; Johansson, Petra P.; Koch, Lauren G.; Britton, Steven L.; Kainulainen, Heikki
Abstract : Key points: Aerobic exercise, such as running, enhances adult hippocampal neurogenesis (AHN) in rodents. Little is known about the effects of high‐intensity interval training (HIT) or of purely anaerobic resistance training on AHN. Here, compared with a sedentary lifestyle, we report a very modest effect of HIT and no effect of resistance training on AHN in adult male rats. We found the most AHN in rats that were selectively bred for an innately high response to aerobic exercise that also run voluntarily and increase maximal running capacity. Our results confirm that sustained aerobic exercise is key in improving AHN. Abstract: Aerobic exercise, such as running, has positive effects on brain structure and function, such as adult hippocampal neurogenesis (AHN) and learning. Whether high‐intensity interval training (HIT), referring to alternating short bouts of very intense anaerobic exercise with recovery periods, or anaerobic resistance training (RT) has similar effects on AHN is unclear. In addition, individual genetic variation in the overall response to physical exercise is likely to play a part in the effects of exercise on AHN but is less well studied. Recently, we developed polygenic rat models that gain differentially for running capacity in response to aerobic treadmill training. Here, we subjected these low‐response trainer (LRT) and high‐response trainer (HRT) adult male rats to various forms of physical exercise for 6–8 weeks and examined the effects on AHN. Compared with sedentary animals, the highest number of doublecortin‐positive hippocampal cells was observed in HRT rats that ran voluntarily on a running wheel, whereas HIT on the treadmill had a smaller, statistically non‐significant effect on AHN. Adult hippocampal neurogenesis was elevated in both LRT and HRT rats that underwent endurance training on a treadmill compared with those that performed RT by climbing a vertical ladder with weights, despite their significant gain in strength. Furthermore, RT had no effect on proliferation (Ki67), maturation (doublecortin) or survival (bromodeoxyuridine) of new adult‐born hippocampal neurons in adult male Sprague–Dawley rats. Our results suggest that physical exercise promotes AHN most effectively if the exercise is aerobic and sustained, especially when accompanied by a heightened genetic predisposition for response to physical exercise. Key points: Aerobic exercise, such as running, enhances adult hippocampal neurogenesis (AHN) in rodents. Little is known about the effects of high‐intensity interval training (HIT) or of purely anaerobic resistance training on AHN. Here, compared with a sedentary lifestyle, we report a very modest effect of HIT and no effect of resistance training on AHN in adult male rats. We found the most AHN in rats that were selectively bred for an innately high response to aerobic exercise that also run voluntarily and increase maximal running capacity. Our results confirm that sustained aerobic exercise is key in improving AHN.